Pengaruh Kegiatan Melipat Kertas (Origami) Terhadap Peningkatan Motorik Halus Anak Usia 4-5 Tahun Di Tk Al Muayyad Dan Tk Islam Bakti Viii - Septiyana, Achmad Prananda, Maskun Pudjianto, SMPh, M.Kes (2016)
Background: Early age is regarded as the golden age ( the golden age) because at that age the child is experiencing enormous development both physically , and psychologically motor. At the age of 4-5 years is a sensitive period in the development of logical thinking aspects of the child , the better the child's fine motor movements make children to be creative like : paper folding , paper cutting , coloring , putting together two sheets of paper , paper weaving. However, not all children have the maturity to master this skill . One media activities that can stimulate the development of fine motor skills of early childhood is the activity of paper folding (origami ). Research purposes: To determine the effect of folding paper origami skills to the development of fine motor skills of children aged 4-5 years . Research methods: This research is a Quasi Experiment or quasi experimental . Design research is a pre and post test two group design compared between the two groups: the treatment group were given the activities of paper folding ( origami ) for 3 weeks , every 1 week conducted three meetings. A tool for fine motor using Bender Gestalt test. Data were analyzed using the Wilcoxon signed rank test to test the effect and influence ujibeda using Man Whitney test . Research result: There is the influence of the activities of paper folding ( origami ) to increase fine motor skills of children aged 4-5 epidemic after a statistical test using Wilcoxon test showed a p- value of 0.001 in the treatment group and the control group getting the p-value of 0.004 . While the influence of different test with man Whitney test showed a p- value of 0.000 .